Pendayagunaan Media Sosial Instagram Dalam Upaya Promosi Perpustakaan Pada Dinas Perpustakaan dan Kearsipan Daerah Jawa Barat - Wibisana K Ramadhan; Doddy Rusmono (Progam Studi Ilmu Perpustakaan UIN Sumatera Utara Medan, 2021)
This research contains about the utilization of social media Instagram in an effort to promote the library at the West Java Regional Library and Archives Service. The purpose of this study was to determine the impact of the use of social media Instagram as a media promotion for libraries in the Regional Library and Archives Office of West Java Province. The method used in this research is qualitative with a case study approach, in which the problems to be studied are not yet clear, holistic, complex and meaningful. The results of this study indicate that the social media account Instagram @dispusipdajabar has utilized Instagram social media in an effort to promote the library at the West Java Regional Library and Archives Service by involving three dimensions of informing, persuading, and influencing. In utilizing Instagram social media in an effort to promote libraries at the West Java Regional Library and Archives Service, it is hoped that DISPUSIPDA JABAR needs to create more innovative content in order to increase publications in library promotion so that more people visit.